2004
DOI: 10.1128/jb.186.15.5062-5077.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Homogentisate Pathway: a Central Catabolic Pathway Involved in the Degradation of l -Phenylalanine, l -Tyrosine, and 3-Hydroxyphenylacetate in Pseudomonas putida

Abstract: Pseudomonas putida metabolizes Phe and Tyr through a peripheral pathway involving hydroxylation of Phe to Tyr (PhhAB), conversion of Tyr into 4-hydroxyphenylpyruvate (TyrB), and formation of homogentisate (Hpd) as the central intermediate. Homogentisate is then catabolized by a central catabolic pathway that involves three enzymes, homogentisate dioxygenase (HmgA), fumarylacetoacetate hydrolase (HmgB), and maleylacetoacetate isomerase (HmgC), finally yielding fumarate and acetoacetate. Whereas the phh, tyr, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
250
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(256 citation statements)
references
References 81 publications
6
250
0
Order By: Relevance
“…4-Hydroxyphenylpyruvate is then further oxidized to homogentisic acid (65). The fact that C. psychrerythraea lacks an ortholog of homogentisate dioxygenase catalyzing the oxidation of homogentisic acid to 4-maleylacetoacetate, a step needed for the complete oxidation of L-Phe to carbon dioxide and water (65), further supports the hypothesis that PAH is not involved in catabolism but in specialized synthesis of metabolites derived from L-Phe and L-Tyr in C. psychrerythraea.…”
Section: Discussionmentioning
confidence: 80%
“…4-Hydroxyphenylpyruvate is then further oxidized to homogentisic acid (65). The fact that C. psychrerythraea lacks an ortholog of homogentisate dioxygenase catalyzing the oxidation of homogentisic acid to 4-maleylacetoacetate, a step needed for the complete oxidation of L-Phe to carbon dioxide and water (65), further supports the hypothesis that PAH is not involved in catabolism but in specialized synthesis of metabolites derived from L-Phe and L-Tyr in C. psychrerythraea.…”
Section: Discussionmentioning
confidence: 80%
“…This pathway involves three enzymes: homogentisate dioxygenase, mal- eylacetoacetate isomerase and fumarylacetoacetate hydrolase. The genes encoding these enzymes appear to form a single transcriptional unit (Arias-Barrau et al, 2004). In the P. aeruginosa PA14 and PAO1 genomes, the genes hmgA, fahA and maiA (putatively encoding these three enzymes) seem to form an operon as well (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that the main pigment molecule was a derivative of homogentisic acid. It is interesting to note that this structure corresponds to the dehydrogenated (oxidized) form of homogentisic acid, the main precursor of melanin in other micro-organisms such as Pseudomonas putida, Vibrio cholerae, Burkholderia cenocepacia and Shewanella colwelliana (Arias- Barrau et al, 2004;Coon et al, 1994;Kotob et al, 1995;Kovach et al, 1995). Thus, the pigment produced by the hmgA mutant will be considered here as a pyomelanin.…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with the narrow effector specificity displayed by other members of the IclR family, with the unique exception of the TtgV regulator, which recognizes a wide range of structurally different effectors (40). The aromatic compounds were tested at 1 mM, as it is generally assumed that at this concentration these molecules can diffuse across biological membranes, making transport theoretically unnecessary (14,(41)(42)(43)(44)(45). Nevertheless, we cannot rule out that the absence of induction could be because of the inability of these compounds to enter the cell.…”
Section: Discussionmentioning
confidence: 99%